Exploring the Effects of Remote Work on Employee Well-being and Job Satisfaction - Megha Bindal; Dr. Radha Krishan Sharma (Educational Administration: Theory and Practice, 2024)
This research uses a quantitative approach to investigate the impact of remote work on workers’ job satisfaction and well-being. For the purpose of gathering information from three hundred professionals working remotely in a variety of fields, a survey questionnaire was used. Important topics such as autonomy, flexibility, work-life balance, job satisfaction, and employee well-being were discussed in the questionnaire which was sent to employees. It has been shown via research that the characteristics of working remotely have a considerable and favorable influence on both well-being and job satisfaction. Work-life balance was shown to be an effective mediator between remote work and good outcomes for workers, while autonomy and flexibility were found to be the most important factors in determining the levels of satisfaction experienced by workers. Due to the fact that both direct and indirect impacts of remote work on workers’ experiences were detected, the PLS-SEM analysis that was performed using Smart PLS in this study is very beneficial. In a broader sense, the study identifies autonomy, flexibility, and work-life balance as the basic factors of satisfaction and well-being. Furthermore, the research experimentally proves the good impacts that telecommuting has for workers.